Beyond consensual domains: Enactivism, social representations and third-order unities. (June 2015) - Sridharan, Vishnu
Although Enactivism and cultural anthropology share many core principles, a satisfactory Enactivist approach to culture has not yet been articulated. While the Enactivist embraces the cultural anthropologist's skepticism with respect to a pregiven world described through objective truths, one of its stumbling blocks has been its difficulty in accounting for the normative background of interpersonal interaction, or what Wolfgang Wagner has referred to as "Social Representations." This article argues that in order for the Enactivist to provide the conceptual tools necessary for this analysis, she must make use of what Varela and others refer to as "third-order unities." The same principles that the Enactivist uses to explain the emergent properties of cells and organisms—autopiesis and identity-production—must be applied at the level of a society in order to understand how cultural meanings emerge and how they influence individual behavior. By applying these concepts at the supra-individual level, we get a more lucid picture of the fundamental features of an Enactivist account of culture, and can better understand the fundamental principles that Enactivism claims underlie all living systems both simple and complex.